2019
DOI: 10.3389/fevo.2019.00169
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Monarch Site Occupancy and Dynamics in Iowa

Abstract: The monarch butterfly (Danaus plexippus) is the focus of large-scale habitat restoration efforts because of recent population declines. From 2006-2017 we monitored monarchs at >400 sites throughout Iowa to link site occupancy and colonization/extinction dynamics to the presence of milkweed, site-specific habitat metrics, and landscape context at differing spatial scales. We used a robust design occupancy model in Program MARK and a hierarchical model selection approach to estimate site occupancy, extinction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 76 publications
(124 reference statements)
0
5
1
Order By: Relevance
“…While the resource concentration hypothesis posits that specialist herbivore insects are more likely to nd and linger within larger habitat patches (Root 1973, Hill et al 1996, we found that patch size did not predict adult monarch density. Previous researchers reported a positive effect of patch size on monarchs (Davis et al 2007, Dinsmore et al 2019. Patch size assessment differed between our study and theirs, which may account for different results.…”
Section: Landscape-level Effectscontrasting
confidence: 90%
See 2 more Smart Citations
“…While the resource concentration hypothesis posits that specialist herbivore insects are more likely to nd and linger within larger habitat patches (Root 1973, Hill et al 1996, we found that patch size did not predict adult monarch density. Previous researchers reported a positive effect of patch size on monarchs (Davis et al 2007, Dinsmore et al 2019. Patch size assessment differed between our study and theirs, which may account for different results.…”
Section: Landscape-level Effectscontrasting
confidence: 90%
“…We used a digital raster-based land cover classi cation map with a grain size of 30 m × 30 m to determine, for a 10 km-radius circular buffer surrounding each survey site, the proportion of grassland habitat (National Land Cover Dataset 2016). The 10-km assessment was chosen to correspond with the estimated daily travel maximum for a female adult monarch (Zalucki 2016, see also Dinsmore et al 2019). Area-based landscape metrics, speci cally the proportion of suitable habitat in the landscape within a given buffer, are reliable metrics of patch isolation when compared to simple distance-based or omni-directional distance-based metrics (Bender et al 2003, Fahrig 2013.…”
Section: Landscape-level and Area-based Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, based on this previous work and our results, we emphasize caution when interpreting results from studies based on targeted sampling strategies and argue for randomization in future studies of long-term monarch population trends to ensure unbiased inference at appropriate spatial scales. It may be worth adding that we included non-random sites in a robust design occupancy analysis (Dinsmore et al, 2019) and argued that the inclusion of these sites was of less concern for presence/absence data than for density or count data (as in this study). This is due to the high occupancy rate of monarchs (often > 0.90), independent of actual counts.…”
Section: Yearmentioning
confidence: 98%
“…Land-use land-cover (LULC) studies describe how land cover, and land use by humans, changes through time and the causes/consequences of those changes. LULC analyses have tracked the status of oyamel fir ( Abies religiosa ) forests supporting monarchs in Mexico 38 42 , identified restoration potential of monarch habitat in the US 43 45 , modelled monarch and milkweed distributions 7 , 46 , 47 , migratory connectivity 48 and threats during migration 49 . Analyses of how LULC may impact monarch habitat in Texas and Mexico, have not, to date, occurred, despite the important role this region plays in the eastern population’s life cycle.…”
Section: Introductionmentioning
confidence: 99%